Comparison of conventional impression making and intraoral scanning for the study of unilateral cleft lip and palate. (24th November 2022) - Okazaki, Tomoyo; Kawanabe, Hitoshi; Fukui, Kazunori
Abstract: Patients with cleft lip and palate (CLP) encounter various problems, including disorders related to feeding, esthetics, and pronunciation. We compared two impression methods, conventional impression making and intraoral scanning, to study unilateral cleft lip and palate (UCLP). Patients with UCLP ( n = 7) were selected, and palatal impressions were taken by two steps: (1) impressions were obtained using an addition silicone rubber impression material, and a plaster model was prepared and (2) optical impressions were obtained using a desktop three‐dimensional (3D) scanner and stereolithography (STL). Data were generated by two impression system combinations through STL. The results were analyzed using the Kruskal–Wallis or Mann–Whitney U test. There were no significant differences in the dimensions of the models between both groups. The measured depth of the alveolar cleft defects was deeper in the plaster model group (STL) than in the intraoral scanner group (STL). Digital models may prevent the risk of aspiration and respiratory disorders by using impression materials for preoperative jaw treatment of newborns and infants. We compared the results of both impression methods in the same patient and found that a shift to the 3D printer model is a safe alternative for preoperative jaw correction, as evidenced from the amount of tissue displaced due to the pressure applied during impression taking. In the future, we would like to conduct clinical research with a larger sample size of CLP patients to further corroborate these findings.